Previsão hidrossedimentológica numa bacia periurbana através do acoplamento de modelos climáticos e hidrológicos - Silva, Richarde Marques da (2005)
The objective of the present study is to develop an integrated system of hydro-meteorological forecasting (rainfall-runoff-erosion) to be applied in information systems to be used by watershed committees. In order to model the rainfall-runoff-erosion forecasting to Pirapama river basin, which is located in the coast of Pernambuco state in northeastern Brazil, it was accomplished the coupling of forecasted rainfall data generated by a nesting between a atmospheric regional circulation model and an atmospheric global circulation model into rainfall-runoff-erosion simulation models. A climate forecast series of 14 years was generated, from 1987 to 2000 for the first six months of each year. That data series was inserted into two hydrologic models. The first one, Açumod, is a rainfall-runoff model that uses distributed parameters, and has as input the precipitation and evapotranspiration data and then the water balance is carried out with a system of reservoirs. The second one, Kineros2, is an event-oriented, physically-based model, which simulates the surface runoff and the sediment yield. The results showed a satisfactory agreement between the computed and observed runoff data using forecasted rainfall data. This study is a first attempt to forecast rainfall-runoff-erosion to Pirapama river basin, and even so, the obtained results showed that this system can be considered a promising tool to runoff-erosion forecasting in watersheds of northeastern Brazil